Mycobacterium tuberculosis Drives Expansion of Low-Density Neutrophils Equipped With Regulatory Activities - La Manna, Marco Pio; Orlando, Valentina; Paraboschi, Elvezia Maria; Tamburini, Bartolo; Di Carlo, Paola; Cascio, Antonio; Asselta, Rosanna; Dieli, Francesco; Caccamo, Nadia (Frontiers in Immunology, 2019)
In human tuberculosis neutrophils represent the most commonly infected phagocyte but their role in protection and pathology is highly contradictory. Moreover, a subset of low-density neutrophils (LDNs) has been identified in TB, but their functions remain unclear. Here, we have analyzed total neutrophils and their low-density (LDNs) and normal-density (NDNs) subsets in patients with active TB disease, in terms of frequency, phenotype, functional features and gene expression signature. Full blood counts from Healthy Donors, Latent TB infected, active TB, and cured TB patients were performed. Frequency, phenotype, burst activity, and suppressor T cell activity of the two different subsets were assessed by flow cytometry while NETosis and phagocytosis were evaluated by confocal microscopy. Expression analysis was performed by using the semi-quantitative RT-PCR array technology. Elevated numbers of total neutrophils and a high neutrophil/lymphocyte ratio distinguish patients with active TB from all the other groups. PBMCs of patients with active TB disease contained elevated percentages of LDNs compared with those of H.D., with an increased expression of CD66b, CD33, CD15, and CD16 compared to NDNs. Transcriptomic analysis of LDNs and NDNs purified from the peripheral blood of TB patients identified 12 genes differentially expressed: CCL5, CCR5, CD4, IL10, LYZ and STAT4 were upregulated while CXCL8, IFNAR1, NFKB1A, STAT1, TICAM1 and TNF were downregulated in LDNs, as compared to NDNs. Differently than NDNs, LDNs failed to phagocyte live Mycobacterium tuberculosis (M. tuberculosis) bacilli, to make oxidative burst and NETosis, but caused significant suppression of antigen-specific and polyclonal T cell proliferation which was partially mediated by IL-10. These insights significantly expand our understanding of the pathogenesis of human TB.